(untitled) - The World Bank (Washington DC, 2009)
This indispensable statistical reference allows you to consult over 900 indicators for some 150 economies and 14 country groups in more than 80 tables. It provides a current overview of the most recent data available as well as important regional data and income group analysis in six thematic sections: World View, People, Environment, Economy, States and Markets, and Global Links. World Development Indicators 2009 presents the most current and accurate development data on both a national level and aggregated globally. It allows you to monitor the progress made toward meeting the Millennium Development Goals endorsed by the United Nations and its member countries, the World Bank, and a host of partner organizations. These goals, which focus on development and the elimination of poverty, serve as the agenda for international development efforts. New feature Statistics help us understand the events that trigger a crisis and measure its impact. Along with this year's 91 data tables,each section of the World Development Indicators 2009 has an introduction that shows statistics in action, describing the history of the current global crisis, its effect on developing economies, and the challenges they face.
Keywords: World development,Developing countries,Nước đang phát triển,Phát triển thế giới; Economic policy,Economic conditions,Điều kiện kinh tế,Chính sách kinh tế